A NOTE ON THE BRAZILIAN BROMELIAD CRABS (CRUST ACEA, GRAPSI DAE) - Abele, Lawrence G. (Arquivos de Ciências do Mar, 2018)
Recently, two authors ( Sattler & Sattler, 1965 and McWilliams, 1969) independently reported on a species of Sesarma Say, 1817 found in Brazil living in water of the basal leaves or tanks of bromeliad epiphytes. Sattler & Sattler (1965) reported the species as Sesarma ricordi H. Milne Edwards, 1853 , and gave notes on its habitat, stomach contents and behavior. McWilliams (1969) reported the species as Sesarma miersii Rathbun, 1897 , and gave notes on its habitat and color.